2021
DOI: 10.1002/ajb2.1650
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of apetaly in the cosmopolitan genus Stellaria

Abstract: Across angiosperms, evolutionary loss of petals has been rampant and characterizes many distantly related lineages (e.g., in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 78 publications
(137 reference statements)
0
11
0
Order By: Relevance
“…The formerly recognized monotypic genus Myosoton, characterized by 5 styles and a capsule dividing into 5 bluntly bidentate teeth, is also nested within this clade, corroborating its synonymy under Stellaria (Harbaugh & al., 2010;Greenberg & Donoghue, 2011;Li & al., 2016;Wang & al., 2017;Sharples, 2019;Sharples & Tripp, 2019a). In a further study, based on phylogenetic analyses and field investigations, Sharples & al. (2021) suggested that petal loss in Stellaria is repeated several times across the clades and is associated mostly with self-pollination.…”
Section: ■ Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The formerly recognized monotypic genus Myosoton, characterized by 5 styles and a capsule dividing into 5 bluntly bidentate teeth, is also nested within this clade, corroborating its synonymy under Stellaria (Harbaugh & al., 2010;Greenberg & Donoghue, 2011;Li & al., 2016;Wang & al., 2017;Sharples, 2019;Sharples & Tripp, 2019a). In a further study, based on phylogenetic analyses and field investigations, Sharples & al. (2021) suggested that petal loss in Stellaria is repeated several times across the clades and is associated mostly with self-pollination.…”
Section: ■ Discussionmentioning
confidence: 95%
“…In a further study, based on phylogenetic analyses and field investigations, Sharples & al. (2021) suggested that petal loss in Stellaria is repeated several times across the clades and is associated mostly with self‐pollination.…”
Section: Discussionmentioning
confidence: 99%
“…This work brings the Stellaria media plant to the fore [6]. This is popularly called chickweed and is part of the Caryophyllaceae family along with other plants such as Stellaria alsine, Stellaria pallida, Stellaria dichotoma, Stellaria nemorum, Stellaria holostea [7,8]. Until now, this Stellaria species is considered to be beneficial in the form of ethanolic, methanolic, and aqueous extracts or even consumed in the daily diet in various conditions such as lung diseases (asthma, bronchitis, bronchiolitis, lung cancer), cancer, skin diseases (burns, cuts, scratches having a healing effect) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In several eudicot families, the recurrent loss of petals considerably increases the variation of flower ground plan ( Endress, 2006 ; Pieper et al, 2016 ). Apart from wind-pollinated lineages, apetaly is especially common among selfing plants since they do not require pollinators ( Culley and Klooster, 2007 ; Sharples et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%